[Pineapple field at the Orange Grove Estate] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Pine field at the Orange Grove Estate, Trinidad, West Indies.
Cataloger's title
Keywords: Pineapple -- Trinidad and Tobago; Pineapple -- Trinidad and Tobago